A quantum cryptography system used to encrypt the Italian Prime Minister’s videocall at ESOF2020 - Vagniluca, Ilaria; Biagi, Nicola; Bacco, Davide; Zavatta, Alessandro (Il Colle di Galileo, 2021)
During the closing ceremony of the EuroScience Open Forum (ESOF2020), held on 6 September in Trieste, Prime Minister Giuseppe Conte took part in a public demonstration of a quantum cryptography protocol, carried out by the Quantum Communications group of the National Institute of Optics of Florence. The demonstration exploited the transmission of quantum states through the LightNet fiber optic network.